Command Style in Al-Aqqad’s Poetry - Saheed Adewale Mikael (Al-Jawhar : Journal of Arabic Language, 2024)
The Arabic language possesses an expressive richness that distinguishes it from other languages, particularly through its various stylistic forms and syntactic structures. One unique style is the command style, which encompasses numerous forms and rich semantic functions. Each form within this command style conveys specific meanings and functions that are contextual within sentence structures. This study focuses on the literary works of Abbas Mahmoud Al-Aqqad, a prominent poet in modern Arabic literature. Al-Aqqad is renowned for his linguistic exploration and creativity in utilizing various stylistic forms, including the command style, which remains not fully understood within the context of poetic aesthetics and semantics. This research sought to analyze the command style in Al-Aqqad’s poetry, aiming to identify the patterns of command compositions, the extent of their usage, and the non-original meanings that emerged through these forms in his poetry. The study is structured into four sections, preceded by an introduction and a preface, and concluded with results and a list of sources and references. At the conclusion of the research, several key findings were noted: the command verb forms derived from the present tense had the most significant presence in his poetry compared to other forms. Additionally, nouns of the command verb, such as (eh) ("go on"), (sah) ("be silent"), and (mah) ("be desist"), were identified as defined and uninflected because the tanween indicates a desire for something unspecified. Furthermore, the four forms of the command style deviated from their original meanings to convey alternative meanings such as seeking, directing, guiding, wishing, making a choice, allowing, regretting, and more.